Comparison of three flood-related relocation programs with probabilistic cost-benefit analyses - Boudreault, Mathieu; Bourdeau-Brien, Michael; Milot, Nicolas (International Journal of Disaster Risk Reduction, 2023)
Many regions are becoming subject to successive flooding and with climate change taking its toll, it is no surprise that we observe a growing interest for risk avoidance strategies such as relocation. Cost-benefit analysis is the dominant tool used by decision-makers to assess flood risk avoidance projects. Yet, few guidelines are available about how to implement such analysis. This paper advocates for a probabilistic cost-benefit analysis and details a step-by-step procedure via a real-world example. The results show that relocation can be a cost-effective strategy for many high-risk properties and neighborhoods. The level of indemnities and the inclusion of intangible losses are two key drivers of profitability. The paper also analyzes three distinct designs of relocation programs. The results reveal that proactive and innovative schemes, such as managed retreat and usufruct arrangements, constitute worthwhile alternatives to a more conventional post-flood response design.
Keywords: Bourdeau-Brien_Michael; Infolettre; Infolettre_Novembre_2023